HOTELROOMRESERVATIONINFORMATION SYSTEMBASEDONTHE AMBASSADORHOTELKOTABUMINorth Lampung - Aris Tantowi; Heryadi . (STMIK Dian Cipta Cendikia Kotabumi, 2014)
Ambassador Hotel is one of the main north Lampung Kotabumi existing hotels in this kotabumi kotabumi ambassador hotel provides a safe and comfortable peginapan .kotabumi ambassador hotel has several employees who have their task - each . Reservation process currently underway in the hotel ambassador is to book with telepone or come directly to the hotel so that guests require a relatively long time to do the reservation process and the data that was obtained was recorded manually.The research method is a method in giunakan SDLC ( System Development Life Cycle ) . This methodology analyzing the development of web information systems in general , domains can be adapted to the particular case analysis section . With SDLC methodology is expected to build a user -user will always see the new Web site , the information is always updating and display designs that are well made.If the Information System Web based hotel bookings can be applied at the ambassador kotabumi akam provide convenience for both hotel guests and hotel employees , hotel guests can book rooms wheresoever and anytime without having to come directly to the hotel , guests can see profiles of hotel facilities such as hotel , room type room amenities , room rates and some photos - the photos on the hotel ambassador kotabumi . And a current hotel employees can be easier to find data karnakan hotel guests in the data - the data room hotel guests who book stored in a database .